Examining the Istinbat Systems of the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah - Jamaluddin, Samsidar; Hannani; Sunuwati; BN, Andi Muh. Taqiyuddin (IAIN Parepare, 2024)
The purpose of this research is to study the Istinbat system of the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah. This research is a qualitative research, the type of research is library research. The data collection method is literature review. The results showed that; Istinbat method of the Fatwa Commission of the Indonesian Ulema Council (MUI) refers to the Qur'an, Hadith, consensus, Qiyas and other legal arguments. In its fatwa, the MUI also does not reject other legal arguments that are not debated by the ulama, such as: istihsan, istishab, sad al-dzari'ah, and other arguments that are still disputed by scholars. The Istinbat method of Nahdatul Ulama Bahtsul Masail Institute implements the concept that Istinbat is not taken directly from the original source, namely the Qur'an and Hadith. However, the extraction of the law is done by dynamically mentatbiqkan (harmonizing) the texts expressed in the book in the context of the problem for which the law is sought. Meanwhile, the istinbat method of tarjih and tajdid assembly refers to the benefit as a priority benchmark without ignoring sociological and anthropological aspects. And in istinbat not bound to a particular school of fiqh.